STRATEGI PENGEMBANGAN AGROINDUSTRI TEMBAKAU NON ROKOK DI KABUPATEN JEMBER - Indra Wardhana, Danu; Nurina Aulia, Anisa; Imer Rita, Asih; Rismawati, Rizki; Riskiyono, Syahroni (Jurnal Agroindustri, 2024)
The tobacco agroindustry in Indonesia has the potential to be developed. Tobacco products and their derivatives are products of high value so that in the economic aspect they have a big involvement in the national economy as a provenience of government revenue (taxes), a foreign exchange, income for farmers, and a provider of employment in the on-farm sector. Despite of its provenience, the presence of tobacco products and their derivatives has been widely opposed by the community in line with increasing public awareness of health. Based on this, it is necessary to diversify processed tobacco products into new products other than cigarettes that have high economic value. However, efforts to develop the non-smoking tobacco agroindustry have problems including the high costs of process technology, farmers' technical knowledge, capital, competition with other regions, and the lack of government’s coordinated strategy to develop the non-smoking tobacco agroindustry. In addition, the competitiveness of the non-smoking tobacco agroindustry is still low, so this study aims to formulate a non-smoking tobacco agroindustry development strategy in Jember Regency. Analysis of research data was carried out using the Exponential Comparison Method, Interpretative Structural Modeling and Analytical Hierarchy Process. The main priority result of the selection of superior non-smoking tobacco agroindustry products is tobacco perfume. The key sub-elements to the element are facilities and infrastructure for the non-smoking tobacco agroindustry such as investment and access to capital for farmers and entrepreneurs; The key sub-elements to the constraints element are the limited capital and technology of the non-smoking tobacco agroindustry; the key sub-elements to the institutional element are local governments; and the key sub-elements in the activity elements carried out are increasing market access and partnerships for non-smoking tobacco products. Alternative strategies to increase market access and partnerships have the highest priority in selecting a development strategy for the tobacco perfume agroindustry.